2015
DOI: 10.1093/eep/dvv007
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal lead exposure is associated with decreased cord blood DNA methylation of the glycoprotein VI gene involved in platelet activation and thrombus formation

Abstract: Early-life lead exposure impairs neurodevelopment and later exposure affects the cardiovascular system. Lead has been associated with reduced global 5-methylcytosine DNA methylation, suggesting that lead toxicity acts through epigenetic mechanisms. The objective of this study is to clarify how early-life lead exposure alters DNA methylation of specific genes, using an epigenomic approach. We measured lead concentrations in urine [gestational week (GW), 8] and erythrocytes (GW 14), using inductively coupled pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…These findings are consistent with the result of a research performed in peripheral blood samples from children of both sexes, where lead-associated changes in DNA methylation showed a significant sex dimorphism [ 48 ]. The increasing number of studies showing that developmental exposure to metals influences DNA methylation in exposed children supports the view that the long-term effects of these agents might be mediated by epigenetic changes [ 49 ]. Recently, epigenetic effects of prenatal lead exposure have been also demonstrated in children; however, there have been no marked differences between the sexes—gender was treated as a confounding factor [ 50 ].…”
Section: Discussionmentioning
confidence: 93%
“…These findings are consistent with the result of a research performed in peripheral blood samples from children of both sexes, where lead-associated changes in DNA methylation showed a significant sex dimorphism [ 48 ]. The increasing number of studies showing that developmental exposure to metals influences DNA methylation in exposed children supports the view that the long-term effects of these agents might be mediated by epigenetic changes [ 49 ]. Recently, epigenetic effects of prenatal lead exposure have been also demonstrated in children; however, there have been no marked differences between the sexes—gender was treated as a confounding factor [ 50 ].…”
Section: Discussionmentioning
confidence: 93%
“…We also investigated the top loci identified by a previous EWAS analysis on prenatal lead exposure and cord blood DNA methylation ( Engström et al 2015 ) based on our data set and found that one of the loci (cg05374025) was significantly associated with prenatal lead exposure in our samples ( ; see Table S13).…”
Section: Resultsmentioning
confidence: 98%
“…A previous study also investigated the epigenome-wide association of prenatal lead exposure with cord blood DNA methylation profiles in a birth cohort in rural Bangladesh ( ) with high environmental lead levels, and the authors identified a set of loci with , among which some were located around the gene glycoprotein VI ( GP6 ) ( Engström et al 2015 ). However, only one of these loci (cg05374025) reached statistical significance in our samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations